Degradation of hexavalent chromium and methyl orange by the synergistic system of graphitic carbon nitride and electron beam irradiation. (January 2022) - Ma, Xijun; Zhou, Yiming; Gu, Shiqi; Mei, Su; Zhu, Guyue; Yu, Min; Wu, Yiqing; Ping, Yuhe; Hong, Kun; Zhang, Jing; Mao, Ping; Wu, Zhengyan
Abstract: Hexavalent chromium (Cr(VI)) and methyl orange (MO) are highly toxic and difficult to treat. Electron beam irradiation (EB) can produce ·OH, H·, ·O2 −, hydrated electron (eaq − ) and other active substances, which have strong redox ability to pollutants. However, the penetration capacity of EB is limited (the penetration depth of water is 10 cm). Therefore, the photocatalytic method of graphitic carbon nitride (CN) was used as the synergistic method of EB in this project to degrade Cr(VI) and MO. The results showed that the maximum treatment efficiency of 100 mg L −1 Cr(VI) and 50 mg L −1 MO with liquid surface height of 5 cm was 95.0% and 99.1%, respectively, which was much higher than that of single photocatalytic method (39.5%, 23.4%) and EB (79.6%, 92.1%), and the efficiency of synergistic treatment was higher under acidic condition. When the liquid depth increased to 30 cm, the efficiency of synergistic system decreased by 14.7% and 15.2% for the degradation of Cr(VI) and MO, respectively, less than the single EB treatment (47.2%, 45.7%). Additionally, the performance of the morphology, the light absorption performance, and the separation of photogenerated electron-hole pairs of the CN were evaluated before and after the synergistic system. Lastly, the mechanism illustrates that the electron and thermal effects of EB, eaq −, photogenerated electrons played key roles for the Cr(VI) reduction, and the electron and thermal effects of EB, ·O2 −, photogenerated holes played key roles for the MO degradation. This study provides a new opportunity for the synergistic system of photocatalyst and EB in the treatment of pollutants. Graphical abstract: Image 1 Highlights: The graphitic carbon nitride was used as the synergy of electron beam irradiation. The synergistic system was applied in the degradation of Cr(VI) and methyl orange. The photocatalytic performance of CN has been changed in the synergistic system. The electron and heat effects of EB were used to study the degradation mechanism. The eaq −, ·O2 −, photogenerated electrons and holes played key roles in the degradation process.